2014
DOI: 10.1117/12.2050160
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian framework with an auxiliary particle filter for GMTI-based ground vehicle tracking aided by domain knowledge

Abstract: In this work, we propose a new ground moving target indicator (GMTI) radar based ground vehicle tracking method which exploits domain knowledge. Multiple state models are considered and a Monte-Carlo sampling based algorithm is preferred due to the manoeuvring of the ground vehicle and the non-linearity of the GMTI measurement model. Unlike the commonly used algorithms such as the interacting multiple model particle filter (IMMPF) and bootstrap multiple model particle filter (BS-MMPF), we propose a new algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Particle filter methods reduce computational complexity and increase accuracy of the estimations by choosing reliable samples from numerous available samples [3][4][5][6][7][8][9][10][11]. It should be noted that Bayesian estimation algorithm is used during the Monte Carlo procedure to calculate an estimation of the prior probability density function for k=1,2, …, instead of calculating the state k x [12][13][14].…”
Section: -Introductionmentioning
confidence: 99%
“…Particle filter methods reduce computational complexity and increase accuracy of the estimations by choosing reliable samples from numerous available samples [3][4][5][6][7][8][9][10][11]. It should be noted that Bayesian estimation algorithm is used during the Monte Carlo procedure to calculate an estimation of the prior probability density function for k=1,2, …, instead of calculating the state k x [12][13][14].…”
Section: -Introductionmentioning
confidence: 99%
“…After the state estimation, for every particle i whose r i k = on-road, the vehicle state vector x projection,i k is converted back to the local coordinate for the VSMM prediction at the next time instance using Eq. (9). The outline of the proposed C-VSMM-PSO-PF algorithm is presented in Algorithm 2:…”
Section: Particles Projection and State Estimationmentioning
confidence: 99%
“…The most widelyused terrain information is the road network, and representative work is shown in [6][7][8][9]. In [6], the road constraint was treated as a pseudo-measurement and incorporated into the extended Kalman filter (EKF) scheme for state estimation of the target moving on the road.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most apparent domain knowledge is the road constraint information such as the constrained region imposed by a road map. Studies on road network-aided ground vehicle tracking have been reported in different works such as [2], [3] and [4]. In these works, different state estimation algorithms (such as the Gaussian (s) approximation filtering method in [2] and [4], and particle filtering method [3]) have been applied together with the road constraint information for the state estimation.…”
Section: Introductionmentioning
confidence: 99%